1996
DOI: 10.1002/j.1460-2075.1996.tb01044.x
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine-599 of the c-Mpl receptor is required for Shc phosphorylation and the induction of cellular differentiation.

Abstract: Interaction of thrombopoietin (TPO) with its receptor, c‐Mpl, triggers cell growth and differentiation responses controlling primitive haemopoietic cell production and megakaryocytopoiesis. To examine the important receptor domains and signal transduction pathways involved in these cellular responses, c‐Mpl cytoplasmic domain truncation and tyrosine substitution mutants were generated. In the myelomonocytic leukaemia cell lines WEHI3B‐D+ and M1, ectopic expression of the wild‐type c‐Mpl receptor induced TPO‐de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 54 publications
3
67
0
Order By: Relevance
“…Mpl Y112 is part of a sequence NHSYLPL where the sequence NHSY comprises the Shc phosphotyrosinebinding (PTB) motif, NXXY (Laminet et al, 1996;van der Geer et al, 1996). Therefore, Shc can bind to Y112 through its PTB motif as previously reported (Alexander et al, 1996;Drachman and Kaushansky, 1997). Two tyrosine residues of the EpoR cytoplasmic domain, Y367 and Y425 are required for the engagement of Gab2 in Epo-induced signaling (Wickrema et al, 1999).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Mpl Y112 is part of a sequence NHSYLPL where the sequence NHSY comprises the Shc phosphotyrosinebinding (PTB) motif, NXXY (Laminet et al, 1996;van der Geer et al, 1996). Therefore, Shc can bind to Y112 through its PTB motif as previously reported (Alexander et al, 1996;Drachman and Kaushansky, 1997). Two tyrosine residues of the EpoR cytoplasmic domain, Y367 and Y425 are required for the engagement of Gab2 in Epo-induced signaling (Wickrema et al, 1999).…”
Section: Discussionmentioning
confidence: 72%
“…Indeed, Shc, Stat5, Cis, SHP2, SHIP1 proteins are all able to bind to this site. It was previously shown that Y112 in mpl receptor was both a site of receptor phosphorylation and a critical residue for the Tpo-dependent phosphorylation of Shc (Alexander et al, 1996), SHIP and Stat3 (Drachman and Kaushansky, 1997). Presumably, Y112 could also be a binding site for multiple proteins, thereby suggesting that multifunctional docking sites comprising speci®c tyrosine residues such as EpoR Y425 or mpl Y112 could exist in cytokine receptors as well as in tyrosine kinase receptors like Met (Bardelli et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well established that TPO stimulation results in activation of JAK2, immediately followed by the tyrosine phosphorylation of numerous signaling molecules, including Mpl, STAT3, STAT5, Cbl, Shc, Vav, Raf-1, Ras, MAPK, SHIP, and phosphoinositol 3-kinase (PI3K). 9,[36][37][38] To investigate the possible role of SFKs in Mpl signaling, we used a cytokine-dependent murine cell line, BaF3, which was engineered to express Mpl on the cell surface. The results presented in this study demonstrate that the addition of TPO to BaF3/Mpl cells results in the activation of Lyn kinase.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] The role of JAK2 is still somewhat controversial since one study reported that JAK2, but not TYK2, is necessary for subsequent signaling events, 15 while others have questioned this view. 16 Regardless of such a dispute, Janus kinases, once activated, phosphorylate a number of substrates, including MPL itself which provides a docking site for SH2-containing proteins, the latent transcription factors such as signal transducers and activators of transcription (STAT) 3 and STAT5, and a number of adapter proteins including SHC and SHP2.…”
Section: Introductionmentioning
confidence: 99%